FEATURES OF COMPARATIVE ESTIMATION OF VARIANTS MODERNIZATION OF AEROTECHNICS - Самков, О. В.; Височанський, А. С.; Качур, С. Ю.; Корнієнко, О. В. (Science-based technologies, 2009)
The method of hierarchies’ analysis has been offered for the purpose of selection the best sample of aviation complex. Based on this method the algorithm of comparative estimation and selection of versions for aeronauti-cal engineering upgrade has been developed.